Effects of increasing total sulfur amino acid:lysine ratio on growth performance of 25 to 50 lb pigs - De La Llata, M.; O'Quinn, P.R.; Woodworth, J.C.; Moser, S.A.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred and fifty pigs were used in a 27-d growth study to determine the appropriate total sulfur amino acid:lysine ratio for 25 to 50 lb pigs. Pigs were blocked by weight (initially 22.5 lb) and allotted to one of 10 treatments arranged in a 2 x 5 factorial with two levels of total dietary lysine (.95 and 1.250/0) and five total sulfur amino acid ratios (.45, .50, .55, .60, and .65% of total lysine). Increasing total lysine from .95 to 1.25% increased ADG and improved FIG. Increasing the total sulfur amino acid:lysine ratio did not affect ADG but improved F/G. These results indicate that the optimal total sulfur amino acid:lysine ratio for the 25 to 50 lb pig is not greater than 55%.
Keywords: Swine; Methionine; Lysine; Nursery pigs